Adsorptive removal of organophosphate pesticides from aqueous solution using electrospun carbon nanofibers - Adesanmi, Bukola O.; Mantripragada, Shobha; Ayivi, Raphael D.; Tukur, Panesun; Obare, Sherine O.; Wei, Jianjun (Frontiers in Chemistry, 2024)
Organophosphate pesticides (OPPs) are widely prevalent in the environment primarily due to their low cost and extensive use in agricultural lands. However, it is estimated that only about 5% of these applied pesticides reach their intended target organisms. The remaining 95% residue linger in the environment as contaminants, posing significant ecological and health risks. This underscores the need for materials capable of effectively removing, recovering, and recycling these contaminants through adsorption processes. In this research, adsorbent materials composed of electro-spun carbon nanofibers (ECNFs) derived from polyacrylonitrile was developed. The materials were characterized through several techniques, including scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier Transform Infrared Spectroscopy (FTIR), Brunauer-Emmett-Teller (BET) analysis, and contact angle measurements. SEM analysis revealed details of the structural properties and inter-fiber spacing variations of the carbon nanofibers. The results revealed that ECNFs possess remarkable uniformity, active surface areas, and high efficiency for adsorption processes. The adsorption studies were conducted using batch experiments with ethion pesticide in aqueous solution. High-Performance Liquid Chromatography -Diode Array Detector (HPLC-DAD) was utilized to quantify the concentrations of the OPP.Various parameters, including adsorbent dosage, pH, contact time, and initial ethion concentration, were investigated to understand their impact on the adsorption process. The adsorption isotherm was best described by the Freundlich model, while the kinetics of adsorption followed a non-integer-order kinetics model. The adsorption capacity of the ECNFs for OPP removal highlights a significant advancement in materials designed for environmental remediation applications. This study demonstrates the potential of ECNFs to serve as effective adsorbents, contributing to the mitigation of pesticide contamination in agricultural environments.